The Relationship between Drug User Stigma and Depression among Inner-City Drug Users in Baltimore, MD - Latkin, Carl (Springer US, 2012)
There is growing awareness of the role of stigma and discrimination in HIV prevention, testing, and medical care. Yet, few studies have examined the stigma associated with using illicit drugs. In the present study, we examined the relationship between social network characteristics, drug user stigma, and depression. Study participants were comprised of 340 individuals who reported cocaine, crack, and/or heroin use in the prior 6 months and were involved in an HIV prevention study. They were recruited through street outreach, referrals, and word of mouth in inner-city Baltimore, MD, USA. The stigma scale was comprised of eight items, such as “how much do you feel ashamed of using drugs?” Depression was assessed with the Center for Epidemiological Studies Depression Scale, using cutoffs of 16 and 20 or greater. In the bivariate analyses, gender, homelessness in the past 6 months, drug user stigma, larger size of drug network, and current use of heroin, cocaine, and crack were all significantly associated with high levels of depression, whereas in the multivariate analyses, only drug user stigma remained significantly associated with depression. The results of this study suggest that drug treatment providers and other professionals who provide services to drug users should consider developing trainings to address drug user stigma. These programs should focus on the attitudes and behaviors of health and service providers toward drug users, among drug users themselves, and among family members and others who provide social support to drug users.